2003
DOI: 10.1212/01.wnl.0000048660.71390.c6
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid antibodies in the CSF

Abstract: Antithyroid antibodies and circulating immune complexes (CIC) were found in the CSF of six patients with Hashimoto's encephalopathy (HE) but not in the CSF of 21 controls. The synthesis of autoantibodies and CIC was intrathecal and their titers were independent of the patients' clinical status or therapy. Their presence in the CSF of patients with acute or subacute encephalopathy may be useful in diagnosing HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 5 publications
1
72
1
4
Order By: Relevance
“…These results suggest that the immune-mediated brain damage is more limited in ataxic HE than in other clinical forms, and that CSF and EEG findings cannot distinguish the cerebellar ataxic form of HE from SCD. Ferracci et al [22] reported finding antithyroid Abs in the CSF of patients with HE and that this finding was useful for diagnosing HE. As in SCD patients, however, anti-TPO Abs were not detected in the CSF of the patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the immune-mediated brain damage is more limited in ataxic HE than in other clinical forms, and that CSF and EEG findings cannot distinguish the cerebellar ataxic form of HE from SCD. Ferracci et al [22] reported finding antithyroid Abs in the CSF of patients with HE and that this finding was useful for diagnosing HE. As in SCD patients, however, anti-TPO Abs were not detected in the CSF of the patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) analysis is abnormal in approximately 80 percent of patients, usually revealing an elevated CSF protein level (9). Unfortunately, the present patient refused the examination, so we could not analyze the patient's CSF.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have shown the presence of anti-thyroid antibodies in the CSF 5 and alpha-enolase antibodies in the serum of patients with Hashimoto' s encephalopathy, suggesting the involvement of an autoimmune mechanism in this condition 6 . However, the role of those antibodies and their pathophysiology are unknown.…”
Section: Discussionmentioning
confidence: 99%